Access-right : the future of digital copyright law - Efroni, Zohar (Oxford University Press, 2011)
Selling point: Develops unique approaches to "information" as subject matter of property regulation and to "access to information" as a possible trigger of private property mechanisms. Surveys the major developments in digital copyright law-making over the past two decades, while answering the questions of how we have gotten so far with copyright law and whether recent developments adhere to some ascertainable pattern or logic. Explains the complex legal terrain of anti-circumvention provisions. It localizes this novel species of rules within the larger picture of copyright's expansion and demonstrates its function within that trend. Explores the claim of overprotection and furnishes a critical analysis of current approaches that offer pointed as well as comprehensive types of solutions to the digital dilemma. Presents an original and thought-provoking regulative model toward a true comprehensive approach to the core problems of digital copyright law. The model demonstrates how traditional principles of private ownership and effective users' rights to access copyrighted materials could coexist within a uniform, coherent and balanced legal scheme.